2006
DOI: 10.2108/zsj.23.393
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Cryptocercus Wood-roaches Based on Mitochondrial COII and 16S Sequences, and Chromosome Numbers in Palearctic Representatives

Abstract: Woodroaches of the genus Cryptocercus are subsocial and xylophagous cockroaches, distributed in North America and Asia. Studies on male chromosome number in Nearctic species have shown that diploid numbers vary from 2n=37 to 2n=47; numbers from Palearctic species were heretofore unknown. Two hypotheses have been proposed to explain the varying number of chromosomes among Nearctic species: the serial reduction hypothesis, and the parallel scenario. We performed phylogenetic analyses of the COII gene in these sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The importance of population genetic structure rather than cellular location is confirmed by the observation that the symbiont, Ishikawaella capsulata, of plataspid stinkbugs (Hemiptera) shows reduced genome size and rapid protein evolution despite its location in the gut lumen rather than within cytoplasm of specialized cells (58). Ishikawaella transmission, which occurs when progeny ingest an inoculum deposited on eggs by the mother, is strictly maternal, resulting in single infections and consequent lack of recombination among lineages.…”
Section: Genomic Decay In Obligate Symbionts and Host Dependencementioning
confidence: 98%
See 1 more Smart Citation
“…The importance of population genetic structure rather than cellular location is confirmed by the observation that the symbiont, Ishikawaella capsulata, of plataspid stinkbugs (Hemiptera) shows reduced genome size and rapid protein evolution despite its location in the gut lumen rather than within cytoplasm of specialized cells (58). Ishikawaella transmission, which occurs when progeny ingest an inoculum deposited on eggs by the mother, is strictly maternal, resulting in single infections and consequent lack of recombination among lineages.…”
Section: Genomic Decay In Obligate Symbionts and Host Dependencementioning
confidence: 98%
“…Such studies have shown repeatedly that nutritional symbionts have evolved in parallel with their hosts, starting with studies of aphids and Buchnera and extending to whiteflies, scale insects, psyllids (54), tsetse flies (55), stinkbugs (56), carpenter ants (57), and cockroaches (58).…”
Section: Hereditary Symbiosis In Animalsmentioning
confidence: 99%
“…Since the diets of these insects lack essential nutrients, they depend on bacteria that are able to synthesize the necessary compounds (Bourtzis & Miller, 2003;Douglas, 1998). In many cases, symbiotic bacteria are transmitted vertically from one generation to the next, resulting in coevolution and cospeciation of hosts and symbionts which is reflected in congruent phylogenies (Bandi et al, 1995;Chen et al, 1999;Lo et al, 2003;Moran et al, 1993;Sauer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous molecular phylogenetic studies have shown that divergent lower-level monophyletic clades on mtDNA gene trees include members of only a single chromosomal race, even though the races themselves may not be monophyletic ( Fig. 1b; Kambhampati et al 1996;Burnside et al 1999;Steinmiller et al 2001;Lo et al 2006;Everaerts et al 2008). Thus, phylogenetic approaches can be used to assign an ''unknown'' individual to a chromosomal race.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, Kambhampati et al (1996) first reported the existence of four chromosomal races within the complex, and Burnside et al (1999) subsequently described them as separate species. However, the basis for their taxonomic subdivision has been questioned, and so it has not been widely adopted (Nalepa et al 2002;Lo et al 2006;Everaerts et al 2008). There are also conflicting reports on the spatial distributions of the four races, which have been described as either strictly allopatric (Burnside et al 1999), parapatric (Nalepa et al 2002;Everaerts et al 2008), or sympatric (Steinmiller et al 2001).…”
Section: Introductionmentioning
confidence: 99%